DESENVOLVIMENTO DE SENSORES NANOESTRUTURADOS EMPREGADOS PARA CONSTRUÇÃO DE LÍNGUA ELETRÔNICA PARA A AVALIAÇÃO DE VINHOS - Júnior, Elvandi da Silva (2020)
In the last decades, with the appearance of Nanoscience, it was possible to develop nanostructured electrochemical sensors, which allow to instantly determine, a universe of substances and compounds, their characteristics, quantities, among others. Nanostructured sensors were developed and tested, involving interfaces of the metal / oxide type, used for the quantification of electrochemical techniques. To these sensors, two commercial sensors were added, one for color detection and the other for measuring temperature, in addition to the development of an electronic system and software for acquiring and processing, in real time, data from the sensors, and with that, becoming the electronic tongue. These systems were obtained by chemical and electrochemical techniques and their performance was evaluated using potentiometric and voltammetric measurements. The tests were carried out in solutions containing only deionized water, mixtures of deionized water with ethanol or caffeic acid or gallic acid, at different concentrations, and in solutions of different types of wines, vinegars and other drinks. It was demonstrated that CeO2 mimics the laccase for the detection of oxidizing substance using an electrochemical technique. The sensors for detecting phenolic antioxidant substances, containing CeO2 nanoparticles immobilized on glassy carbon electrodes or on electrically conductive glass sheets coated with ITO or the ethanol detection sensor, consisting of thin films of Cu2O electrodeposited on glass sheets coated with ITO, proved to be efficient and with a great response. In the end, the electronic tongue proved to be viable for the detection of pH, ethanol, phenolic compounds, color and temperature in wines and other drinks.